Exploring Mechanisms of Diabetes-Related Macrovascular Complications: Role of Methylglyoxal, a Metabolite of Glucose on Regulation of Vascular Contractility - Masashi Mukohda; Muneyoshi Okada; Yukio Hara; Hideyuki Yamawaki (Elsevier, 2012)
Methylglyoxal (MGO) is a metabolite of glucose. MGO binds to and modifies arginine, lysine, and cysteine residues in proteins, which leads to formation of a variety of advanced glycation end-products (AGEs) such as argpyrimidine and Nε-(carboxyethyl)lysine. The concentration of MGO significantly increases in plasma from diabetic patients. Increased plasma MGO level seems to be associated with diabetic microvascular complications. In addition, MGO accumulates in large vascular tissues from spontaneous hypertensive rats, which is associated with increased blood pressure. Although it is logical to hypothesize that MGO could directly affect vascular reactivity, available reports are very limited. Our group has examined effects of MGO on vascular reactivity (contraction and relaxation) and explored underlying mechanisms. In this review article, we summarized our recent findings on 1) short-term effects of MGO, 2) long-term effects of MGO, and 3) effects of MGO accumulation in arterial walls on vascular reactivity. These findings may provide further mechanistic insights into the pathogenesis of diabetes-related macrovascular complications including hypertension. Keywords:: glucose metabolite, diabetes, hypertension, vascular reactivity, reactive oxygen species